THE EFFECT OF EMPLOYEE ENGAGEMENT, WORK LIFE BALANCE AND QUALITY OF NURSING WORK LIFE ON THE PERFORMANCE OF INPATIENT NURSES AT BHAYANGKARA HOSPITAL, CLASS IV, MAMUJU - Aziz, Abdul; Susanto, Effri; Pangkey, Dicky Yulius; Rosidawati, Rosidawati (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2025)
Nurses play an essential role in hospitals, particularly in inpatient care, where they are the primary point of contact with patients. As the largest group in the healthcare workforce, nurses interact with patients more than any other healthcare professionals. Despite their crucial role, complaints regarding nurse performance remain frequent among patients and their families. This is evident from the feedback received about hospital services, especially concerning the quality of nursing care. To address this issue, improving nurse performance requires practical strategies, such as enhancing employee engagement, work-life balance, and the overall quality of nursing work life. These factors have been shown to positively influence nursing performance. The aim of this study was to eval_uate how employee engagement, work-life balance, and nursing work life quality affect the performance of inpatient nurses at Bhayangkara Hospital in Mamuju. Using a quantitative non-experimental research design with cross-sectional analysis, the study utilized linear regression to analyze data from 43 inpatient nurses. The data was processed using SPSS Version 24.0. The findings revealed that employee engagement has a significant positive impact on nurse performance, with a p-value of 0.003 (<0.05), thus confirming that greater engagement enhances performance. Work-life balance also significantly influences nurse performance, with a p-value of 0.006, highlighting its importance. Similarly, the quality of nursing work life was found to positively affect performance, with a p-value of 0.009. The F test results indicated that the combined factors of employee engagement, work-life balance, and nursing work life quality significantly influence nurse performance, with a p-value of 0.004. Together, these factors explained 78.6% of the variance in nurse performance, suggesting that other external factors account for the remaining 21.4%.